ANALISIS ALIH KODE DAN CAMPUR KODE PADA FILM “LAYANGAN PUTUS” KARYA BENNI SETIAWAN - Ayu, Ayu Yasni Waruwu (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This research aims 1) to find out the forms of code switching and code mixingin the film “Layangan Putus” by Benni Setiawan in episodes 1 to 5, 2) to find out the reasons for the use of code switching and code mixing in the film “Layangan Putus” by Benni Setiawan in episodes 1 to 5. This type of research is qualitative descriptive research. The data in this research are: secondary data the source of data in this research is the film “Layangan Putus”. Data collection techniques in this research are watching techniques, reading techniquesand note-taking techniques. The data analysis techniques in this research is data reduction, data display, and drawing conclusions/verification.the conclusion is that in the film “Layangan Putus” there are extreme forms of code switching, there are six data and factors for the occurrence of code switching, namely the interlocutor, for mere prestige,the speaker and the speaker personality, the speaker while the formsof code mixing by inserting word elementsare eleven data and formsof code mixing, including eleven repetitions of words, as well as the reason that encourage code mixing namely role identification, identification of various desires to explain or interpret. Sugestions 1) for future researchers, this research should be used as a reference to enrich and increase knowledge about study of code mixing and code switching as well as a source of informations that can support the development of similar research. 2) for students, increasing knowledge and cultivating curiosity is not only being a recipient of knowledge but also being able to become a producer of thoughts about the oral discourse contained in the film “Layangan Putus” regarding forms of code mixing and code switching and their use that occurs in leaming language